Progesterone blockade of a luteinizing hormone surge blocks luteinizing hormone-releasing hormone Fos activation and activation of its preoptic area afferents - Le, Wei-Wei; Attardi, Barbara; Berghorn, Kathie A; Blaustein, Jeffrey; Hoffman, Gloria E (Brain research, 1997)
Progesterone is capable of facilitating or blocking the luteinizing hormone (LH) surge, depending on the timing of its administration. However, the precise targets of progesterone's actions are unknown. Since recent studies described the presence of a periventricular preoptic area (pePOA) neuron population afferent to LH-releasing hormone (LHRH) neurons that is co-activated to express c-Fos with LHRH neurons at the time of the LH surge, the present study was designed to determine if the pePOA neurons contain progesterone receptors (PRs) and whether progesterone inhibition is manifested by a failure of LHRH and pePOA neurons to become activated at the time of an LH surge. For progesterone facilitation, a group of immature rats each received a silastic capsule (1.57 mm i.d., 3.18 mm o.d., 1.5 cm long) containing estradiol-17 β (E 2) in peanut oil (150 μg/ml) at 09.00 h on postnatal day 28 followed 24 h later by a progesterone implant (crystalline, 1.57 mm i.d., 3.18 mm o.d., 1.5 cm long). For progesterone inhibition, a second group of rats received the estrogen capsule and a progesterone capsule (3.35 mm i.d., 4.65 mm o.d., 3.0 cm long) together at 09.00 h on day 28, and 24 h later received only a blank capsule. On the afternoon of postnatal day 29, all animals were anesthetized and perfused for localization of c-Fos and LHRH, PRs alone, or c-Fos and PRs. The present studies determined that following a progesterone-inhibition paradigm, along with blockade of the LH surge, both activation of LHRH and pePOA neurons was low or absent. Staining of PRs in progesterone-facilitated and progesterone-inhibited rats indicated that the pePOA neurons contained PRs in similar patterns. Double labeling of c-Fos and PRs in progesterone-facilitated rats indicated that nearly all the c-Fos-positive neurons of the pePOA (80±4.2%) co-expressed PRs; in progesterone-inhibited rats, only 32±12% of few c-Fos-positive neurons also contained PRs. In no instance were LHRH neurons found to contain PRs. Taken together, these data suggest that both progesterone facilitation and inhibition likely involve direct actions of progesterone on the pePOA neurons, and are consistent with a role for the pePOA neurons in transducing steroid effects on LHRH neurons.